2013
DOI: 10.1093/ageing/aft129
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vestibular dysfunction is prevalent in older adults experiencing multiple non-syncopal falls versus age-matched non-fallers: a pilot study

Abstract: vestibular dysfunction is significantly more prevalent in older adult fallers versus non-fallers. Individuals referred to a falls clinic are older, more impaired and report more falls than those referred to a neuro-otology department. A greater awareness of vestibular impairments may lead to more effective management and treatment for older adult fallers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 22 publications
2
61
0
1
Order By: Relevance
“…31 Although these are non-specific symptoms and may be due to multiple pathologies (i.e. anxiety, orthostatic hypotension), it is plausible some of our patients had an undiagnosed vestibular disorder.…”
Section: Discussionmentioning
confidence: 89%
“…31 Although these are non-specific symptoms and may be due to multiple pathologies (i.e. anxiety, orthostatic hypotension), it is plausible some of our patients had an undiagnosed vestibular disorder.…”
Section: Discussionmentioning
confidence: 89%
“…The evidence base is so strong in showing that 80 per cent of elderly patients presenting to accident and emergency with unexplained falls have vestibular impairment [1]. Elderly patients presenting with multiple falls not caused by syncope have peripheral vestibular impairment in 80 per cent of fallers [2]. Use of cost -effective and evidence based interventions such as Epley's manoeuvre [5] and up-coming interventions such as optokinetic chart stimulation [9,10] is recommended to reduce costly unrecognised vestibular impairment in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients presenting with multiple falls not caused by syncope have peripheral vestibular impairment in 80 percent of fallers [2]. Unrecognised BPPV leads to activity limitations, falls and depression [3].…”
Section: Introductionmentioning
confidence: 99%
“…[3] A case-control study in the UK, in a sample of 56 adults, found that the prevalence of vestibular impairment in older adults who fall was 80%, compared with 19% in age-matched non-fallers. [4] But there are some proposed adaptations that may then reduce the incidence of falls. [5,6,7,8,9] According to Gutman et al [10] , balance is when "all the forces acting on the body are balanced in such a way that the center of mass (COM) is within the limits of stability (LOS)".…”
Section: Introductionmentioning
confidence: 99%